2004
DOI: 10.1039/b316219b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (2S,3S)-3′-fluoroisoleucine

Abstract: The fluorinated amino acid, (2S,3S)-3'-fluoroisoleucine 3, has been synthesised by a route involving stereoselective cuprate or photochemical addition to the compound 4, derived in turn from (2S)-pyroglutamic acid. This provides a reporter group for the hydrophobic amino acid (2S)-isoleucine for use in protein studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…On the one hand first-principle calculations can help in understanding the equilibrium solid-liquid structure. Such calculations have recently been performed for KDP 7 and were found to be in promising agreement with the experimental results. The other approach is through Molecular Dynamics simulations using effective potentials to describe the interactions between the various components in the growth system.…”
Section: Closing the Gap?supporting
confidence: 65%
See 1 more Smart Citation
“…On the one hand first-principle calculations can help in understanding the equilibrium solid-liquid structure. Such calculations have recently been performed for KDP 7 and were found to be in promising agreement with the experimental results. The other approach is through Molecular Dynamics simulations using effective potentials to describe the interactions between the various components in the growth system.…”
Section: Closing the Gap?supporting
confidence: 65%
“…density-functional theory and such results are starting to appear only now. 7 All in all it can be stated that computer modelling is slowly gaining territory in the complexity direction, but only on small systems and with several parameters from real systems still left out.…”
Section: Introductionmentioning
confidence: 99%
“…To gain further evidence for this assignment, the 13 C-1 H coupling constants from a 1 H-coupled 13 C NMR experiment were examined. Typically a proton cis to a carbonyl group in an a,b-unsaturated ester will have a much smaller coupling (4)(5)(6)(7)(8)(9)(10) to the carbonyl carbon than a proton trans (10)(11)(12)(13)(14)(15)(16)(17)(18). 7 Despite this being a welldocumented coupling, measurements of this type have rarely been used to assign the geometry in acrylate derivatives.…”
Section: Papermentioning
confidence: 99%
“…The combined organic layers were dried (MgSO 4 ), filtered, and concentrated in vacuo to give the title compound (2.7 g, 85%) as a white solid; mp 73-74 °C [Lit. 16 [a] D 23 -24.0 (c 2.0, MeOH) [Lit. MeOH)].…”
Section: (2s4r)-2-(tert-butoxycarbonylamino)-4-methylpentan-15-dioimentioning
confidence: 99%
“…It was shown that irradiation of L-isoleucine in either trifluoroacetic acid (TFA) or 50% sulfuric acid in the presence of chlorine gave the L-5-chloroisoleucine which was not purified but treated directly with base to give a concise synthesis of trans-L-3-methylproline in 33% yield [32]. Whilst this chapter is focused on the synthesis of bromo-, chloro-, and iodo-a-amino acids, it is pertinent to note that in 2004 Young et al reported the stereoselective synthesis of (2S,3S)-3 0 -fluoroisoleucine from (S)-pyroglutamic acid for incorporation into ubiquitin to study protein interactions ( [33] and references cited therein).…”
mentioning
confidence: 99%